SISTEM INFORMASI KEHADIRAN SISWA DENGAN MENGGUNAKAN BARCODE BERBASIS WEB (Studi Kasus: SMK Negeri 2 Indramayu) (Program Studi Teknik Informatika Universitas Muhammadiyah Cirebon, 2022)
In the current era of globalization, the role of information technology is very supportive of various educational activities. Currently, a computerized information system is a major requirement for various agencies in processing various data. The current student attendance system at SMK Negeri 2 Indramayu has not been going well because the system used is still manual such as the vice principal of the student department waiting for a student attendance report from the administrative staff of the student department which takes approximately 2 days. This causes the information received by the vice principal of the student affairs section to be less effective. With the existing problems, the researcher proposes a web-based student attendance system using barcodes, the development method used in this study is to use the SDLC (System Development Life Cycle) system, programming language using PHP with user interface using Notepad ++ and MySQL as its database. The proposed system can make it easier for users to find information and compile student attendance reports properly, report formats are neater, student attendance data security is guaranteed because of the login menu. Keyword: Information System, barcode, student attendance, web